Analisis Pemilihan Marketplace Terbaik pada Masa Pandemi COVID-19 Menggunakan Metode Simple Additive Weighting (SAW), Technique for Others Reference by Similarity to Ideal Solution (TOPSIS) dan Weighted product (WP) - Zahra Wafda Syamila; Fauziah Fauziah; Novi Dian Natashia (KITA Institute, 2021)
Marketplace is an online media that functions as a place where sellers and buyers conduct business activities or transactions. The presence of a marketplace is very much needed by the community, especially during the COVID-19 pandemic. The appeal for social distancing makes most people choose to shop online which of course has a big impact on the presence of the marketplace. Because consumer needs continue to increase, the best marketplace Platform that can meet daily needs is needed, through a decision support system using the SAW (Simple Additive Weighting) method, TOPSIS (Technique for Others Reference by Similarity to Ideal Solution) and WP (Weighted product). give the best decision in choosing a marketplace site. In the results of manual and application calculations, it is found that the results are both compatible. In the SAW method, TOPSIS and WP produced the same ranking, namely the Shopee marketplace got the highest ranking with a value of 0.9724 on the SAW method 0.706 on the TOPSIS method and 0.2112 on the WP followed by Tokopedia, Lazada, Bukalapak, and Blibli.